PanelWhiz - Efficient Data Extraction of Complex Panel Data Sets: An Example Using the German SOEP - John P. Haisken-DeNew; Markus H. Hahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper outlines a panel data retrieval program written for Stata/SE 10 or better, which allows easier accessing of complex panel data sets. Using a drop-down menu and mouse click system, the researcher selects variables from any and all available years of a panel study. The data is automatically retrieved and merged to form a "long file", which can be directly used by the Stata panel estimators. The system implements modular data cleaning programs called "plugins". Yearly updates to the data retrievals can be made automatically. Projects can be stored in libraries allowing modular administration and appending. The paper exemplifies the power of PanelWhiz using the example of the German SOEP (German Socio-Economic Panel Study).
Keywords: C81; C87; C23; 330; Panel data; storage; retrieval